Effects of soya bean extract, bisphenol A and 17 beta-estradiol on the testis and circulating levels of testosterone and estradiol among peripubertal juvenile male sprague-dawley rats - Norazit, A.; Mohamad, J.; Razak, S.A.; Abdulla, M.A.; Azmil, A.; Mohd, M.A. (Penerbit Universiti Kebangsaan Malaysia, 2012)
In this study, juvenile male Sprague-Dawley rats (PND 22) were fed with soya extract, bisphenol A, and 17 beta-estradiol, respectively by oral gavage to determine the potential effect on the morphology of their reproductive organs and their hormonal levels. After three weeks of treatment (PND 43), all animals were sacrificed and the blood and testes were collected. All the three treatment groups showed histological differences in testes morphology compared to the control. Animals treated with soya extract and bisphenol A showed a decrease in circulating estradiol levels while animals treated with 17 beta-estradiol showed elevated circulating levels of estradiol. Only the animals treated with soya extract showed elevated levels of circulating testosterone. The results of the present study showed that, soya extract, bisphenol A, and 17 beta-estradiol can alter the histological structure of the testes and influence circulating steroidal hormone levels.